2017
DOI: 10.21273/hortsci11612-16
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Calcium Applications Do Not Improve Quality or Shelf Life of Strawberry, Raspberry, Blackberry, or Blueberry Fruit

Abstract: Foliar calcium (Ca) products are applied by many berry growers to enhance fruit quality and shelf life without evidence that these applications increase fruit Ca or impact fruit characteristics when applied at rates recommended on the product label. The objectives of this study were to determine if fruit or leaf Ca increases when several formulations of liquid Ca products are applied to developing fruit, and to assess any resulting changes in fresh market quality of berries. Products were applied in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…In addition, applying Ca during Phase I of berry development (rapid cell division), when Ca is more readily absorbed into young fruit from the transpirational stream, may more effectively increase Ca concentrations in leaves and fruits (Biddulph et al, 1959;Milthorpe and Moorby, 1969). The results of this study support those of Vance et al (2017), who found foliar Ca applications did not increase leaf or fruit Ca concentrations and had no impact on fruit quality and shelf life in blueberry and other small fruit crops [blackberry (Rubus L. subgenus Rubus), strawberry (Fragaria •ananassa), and red raspberry (Rubus idaeus)] grown in Oregon. The investigators in this study targeted applications to the later phases of fruit development, with Ca applications starting at the early green fruit stage and were repeated three or four times per year.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, applying Ca during Phase I of berry development (rapid cell division), when Ca is more readily absorbed into young fruit from the transpirational stream, may more effectively increase Ca concentrations in leaves and fruits (Biddulph et al, 1959;Milthorpe and Moorby, 1969). The results of this study support those of Vance et al (2017), who found foliar Ca applications did not increase leaf or fruit Ca concentrations and had no impact on fruit quality and shelf life in blueberry and other small fruit crops [blackberry (Rubus L. subgenus Rubus), strawberry (Fragaria •ananassa), and red raspberry (Rubus idaeus)] grown in Oregon. The investigators in this study targeted applications to the later phases of fruit development, with Ca applications starting at the early green fruit stage and were repeated three or four times per year.…”
Section: Discussionsupporting
confidence: 74%
“…Calcium in other fruits, such as apples (Malus domestica), has been shown to enter fruit while young and transpiring, possibly due to an increased stomatal number or function during the first weeks of fruit growth and development (Schlegel and Sch€ onherr, 2002;Wilkinson, 1968). Targeting the dynamic growth phase during early bloom and fruit set did not appear to sufficiently increase fruit nutrient levels in blueberry, and this may be due to a reduced number or function of stomata in early fruit development; stomatal function in blueberry leaves and fruit are not fully understood (Vance et al, 2017). Sufficient Ca may not have been applied after fruit set and during the initial phases of berry development to observe an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although Strik and Vance (2015) found considerable variation in leaf and fruit Ca concentrations, there did not appear to be a relationship in these values for either cultivar. In addition, foliar applications of Ca at manufacturer recommended rates have not been found effective to increase fruit Ca concentration (Arrington and DeVetter, 2017;Vance et al, 2017), likely due to the relatively short time that stomates are functional in blueberries and the impact on Ca uptake through the xylem (via transpiration) in the fruit (Yang, 2018). Although the use of feather meal increased fruit Ca concentration in this trial relative to fish solubles (Fernandez-Salvador, unpublished data), the relationship between leaf and fruit Ca concentrations was inconsistent with both negative and positive correlations in 'Liberty' and 'Duke', respectively, in 1 out of 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…defects such as spotting caused by product application, soft fruit, or splitting (in 'Legacy') could contribute to a lower rating. Ten randomly selected berries per experimental unit were used to determine average berry weight and skin toughness [method described in Vance et al (2017) (Correx 50-g tension gauge; Wagner Instruments, Greenwich, CT)]. These same berries were homogenized to measure TSS using a Palette temperature-compensating digital refractometer (Atago USA, Bellevue, WA).…”
Section: Methodsmentioning
confidence: 99%